ANALYSIS OF THE VALIDITY OF THE DEBT SYSTEM IN THE MONTASIK COMMUNITY, ACEH BESAR, BASED ON FIQH MUAMALAH DOCTRINE - Sucianda, Riska; Sulfanwandi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article examines the legitimacy of debt and receivables in the context of harvest agreements from the perspective of fiqh muamalah. It concentrates on debt agreements that involve rice harvests, in which the lander provides farmers with funds in exchange for a guarantee upon harvest. It is the objective of this investigation to ascertain the system of debt and receivables through harvest agreements in Islamic jurisprudence and to investigate the practice of debt and receivables through harvest agreements in Montasik Subdistrict, Aceh Besar Regency. The research design is legal-empirical. Data was acquired through observations and interviews. However, the study's findings suggest that the implementation of these agreements has been advantageous for the lander and detrimental to producers. Benefits from the pledged products are realized during the debt repayment process, which is characterized by a distinct pricing mechanism. One of the valid conditions for a debt agreement is the fulfillment of the elements of debt, which means that the pledged products must not generate profit. If any of these components are not met, the debt agreement is rendered null and void.